2005
DOI: 10.1097/01.sla.0000157317.60536.08
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Histologic Vascular Invasion in Papillary Thyroid Carcinoma

Abstract: In papillary carcinoma, it should be noted that histologic vascular invasion may be considered as a sign of an increased tendency toward hematogenic invasion and consequent increase in the relative percentage of metastases; ultimately, this means a poorer prognosis. In the presence of risk factors indicating a possible increase in biologic aggressiveness, adequate postoperative treatment and close follow up become essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 19 publications
(19 reference statements)
8
84
0
5
Order By: Relevance
“…Our findings revealed that low risk group had better prognosis than intermediate and high risk. This result was similar to many publish studies (McConahey et al, 1986;Gemsenjager et al, 2001;Falvo et al, 2005;Lang et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…Our findings revealed that low risk group had better prognosis than intermediate and high risk. This result was similar to many publish studies (McConahey et al, 1986;Gemsenjager et al, 2001;Falvo et al, 2005;Lang et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…[10][11][12][13][31][32][33] Nishida et al 33 reported vascular invasion in 46.9% of papillary thyroid carcinomas and distant metastases in only 8% of angioinvasive papillary thyroid carcinomas, suggesting that the criteria applied were not specific enough to identify high risk patients. Our review identified rigid criteria of vascular invasion in only 3% of thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors tend to invade vessels to obtain abundant oxygen and nutrients for cell metabolism and proliferation-associated biosynthesis. Clinical studies have confirmed that patients with vessel invasion by tumors had an increased risk of recurrence and a poorer prognosis compared with those who had tumor-free vessels in a range of cancers, including breast cancer, hepatocellular carcinoma and papillary thyroid carcinoma (23)(24)(25). In addition, in patients without pre-operative metastasis, resection of the tumor-invaded vessels conferred a survival benefit, with a similar long-term prognosis compared with patients without vessel invasion by tumors (26,27).…”
Section: Hypothesismentioning
confidence: 65%